Development of a Ventilatory Classification System in Patients With Heart Failure - Arena, Ross; Myers, Jonathan; Abella, Joshua; Peberdy, Mary Ann; Bensimhon, Daniel; Chase, Paul; Guazzi, Marco (Circulation (New York, N.Y.), 2007)
Background— Ventilatory efficiency, commonly assessed by the minute ventilation (V̇ e )–carbon dioxide production (V̇ co 2 ) slope, is a powerful prognostic marker in the heart failure population. The purpose of the present study is to refine the prognostic power of the V̇ e /V̇ co 2 slope by developing a ventilatory class system that correlates V̇ e /V̇ co 2 cut points to cardiac-related events. Methods and Results— Four hundred forty-eight subjects diagnosed with heart failure were included in this analysis. The V̇ e /V̇ co 2 slope was determined via cardiopulmonary exercise testing. Subjects were tracked for major cardiac events (mortality, transplantation, or left ventricular assist device implantation) for 2 years after cardiopulmonary exercise testing. There were 81 cardiac-related events (64 deaths, 10 heart transplants, and 7 left ventricular assist device implantations) during the 2-year tracking period. Receiver operating characteristic curve analysis revealed the overall V̇ e /V̇ co 2 slope classification scheme was significant (area under the curve: 0.78 [95% CI, 0.73 to 0.83], P <0.001). On the basis of test sensitivity and specificity, the following ventilatory class system was developed: (1) ventilatory class (VC) I: ≤29; (2) VC II: 30.0 to 35.9; (3) VC III: 36.0 to 44.9; and (4) VC IV: ≥45.0. The numbers of subjects in VCs I through IV were 144, 149, 112, and 43, respectively. Kaplan-Meier analysis revealed event-free survival for subjects in VC I, II, III, and IV was 97.2%, 85.2%, 72.3%, and 44.2%, respectively (log-rank 86.8; P <0.001). Conclusions— A multiple-level classificatory system based on exercise V̇ e /V̇ co 2 slope stratifies the burden of risk for the entire spectrum of heart failure severity. Application of this classification is therefore proposed to improve clinical decision making in heart failure.